Detection of some auto antibodies of Celiac disease in Sera of patients with Chronic Hepatitis B virus - G.Abid, Shiamaa.; S.Aboud, Rana.; Abudl-Razak, Safa.A. (Iraqi Journal of Science, 2023)
To determine the relationship between chronic hepatitis B virus and autoimmune celiac disease, seventy five patients with chronic hepatitis B virus of ages (8-70) years have been investigated and compared to 50 healthy individuals. All the studied groups were carried out to measure anti-tissue transglutaminase antibodies IgA and IgG by ELISA test and anti-endomysial antibodies IgA and IgG by IIFT. There was a significant elevation in the concentration of anti-tissue transglutaminase antibodies IgA and IgG compared to control groups (P< 0.01) .The prevalence of antiTtG IgA and IgG was 14.67% and 12.0% respectively.There was a highly significant difference (P<0.01) when compared between studied groups .While the prevalence of anti-endomysial antibodies IgA and IgG was 9.33% and 4.0% respectively. There was a highly significant difference(P< 0.01) when compared between studied groups. These results indicated that infection with chronic hepatitis B virus may play an important role in pathogenesis of celiac disease.